Anthropological perspectives on genomic data, genetic ancestry, and race. (14th December 2019) - Benn Torres, Jada
Abstract: Human variation, including questions about race, have been central to biological anthropology since its emergence as a professional discipline in the early 20th century. More recently, genomic data have been used to address open questions about the nature and scope of human variation. Results from genome‐wide association studies and commercially available direct‐to‐consumer genetic ancestry tests have also kindled scholarly debate about the relationship between genetics/genomics and race. Such discussions among scholars and other stakeholders, illustrates that there are still many open issues about how genomic data influence the ways that people think about and debate race and racism. Genetic ancestry remains particularly contentious because of a complicated history of race within anthropology and other human sciences. In this article, I provide a broad overview on understandings of race given the new discoveries in genetics/genomics and provide examples of how these types of data continue to impact social and legal understandings of race. Ultimately, given that a primary focus of biological anthropology is to query human experience from a biological perspective, it will remain critical that biological anthropologists uphold the anti‐racist tradition of modern anthropology and diligently work to shape narratives about human difference.